THE STAKEHOLDER APPROACH APPLIED TO ORGANIZATIONAL PERFORMANCE MEASURING SYSTEMS - HAIROUT, Widad (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Performance is a central concept of organizational theories whose purpose is to develop knowledge that can improve the functioning of the organization and subsequently its performance. However, despite its weight in these theories, organizational performance remains among the most controversial concepts in this area. Several theoretical frameworks have been mobilized to study it, the approach of the stakeholders seems to be the most adapted to the current organizational context. It is based on the design of the organization as an open system and emphasizes the satisfaction of the organization’s stakeholders as a condition of organizational performance. The financial approach that offered measurement solutions, showed its limits in the face of this new context, the traditional systems of measurement of organizational performance (OPMS) were therefore questioned leading to reflections in the researchers during over the last three decades, how can these tools be adapted to organizational strategies and the economic environment. The purpose of this paper is to present the different approaches to conceptualizing performance in the literature and the evolution of performance measurement systems in the light of the stakeholder approach. Keywords Organizational performancesystem of measurement of organizational performancefinancial approachstakeholder approachcybernetic modelhostile model.